Heterogeneity Management Using OAEI Benchmark Dataset - Ramar, Kaladevi; ., . (International Journal of Engineering and Technology, 2018)
The evolution of ontologies and itsapplications are in various fields like artificial intelligence, reasoning, philosophy, biological science, and medical field. The components of ontologiesare concepts, instance, relationships, constraints, axioms and inference mechanism. Ontology is a main source for enabling interoperability in the semantic web. In this paper heterogeneities are identified between information systems and the possible rectification are carried out using OAEI benchmark datasets. Proposed method is compared with S-Match algorithm. The evaluation results shows that proposed method is performed better and structure changes of input ontologies not affect the results.Â Â